Studi Literatur: Pengaruh Pelatihan dan Pengembangan Karir terhadap Kinerja Pegawai Puskesmas - Rini Andriani; Rinawati MM (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Training and career development play a crucial role in improving the performance of health center (puskesmas) employees to deliver optimal healthcare services. This study aims to analyze the influence of training and career development on employee performance at puskesmas and to identify challenges in their implementation. The method used is a literature review with a descriptive-analytical approach based on previous studies related to training, career development, and human resource performance in the health sector. The results show that relevant and continuous training enhances employee efficiency, accuracy, and mental readiness, while clear and sustainable career development increases motivation, loyalty, and employee engagement. The synergy between training and career development is key to successfully improving employee competence and motivation sustainably. However, program implementation faces challenges such as budget constraints, lack of policy support, geographic barriers, and less operational HR development policies. Therefore, strategic and integrated HR management is essential to improve the quality of healthcare services at puskesmas.